2014
DOI: 10.1210/jc.2014-1452
|View full text |Cite
|
Sign up to set email alerts
|

Sex Steroids in Relation to Sexual and Skeletal Maturation in Obese Male Adolescents

Abstract: Obese boys have lower circulating SHBG and TT, but similar FT concentrations during mid and late puberty in parallel with a normal pubertal progression and serum PSA levels. Our data indicate that in obese boys, serum FT concentration is a better marker of androgen activity than TT. On the other hand, skeletal maturation and E2 were increased from the beginning of puberty, suggesting a significant contribution of hyperestrogenemia in the advancement of skeletal maturation in obese boys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 33 publications
9
45
0
Order By: Relevance
“…This explains why patients with aromatase deficiency resulting from inactivating mutation of the aromatase gene show undetectable levels of E 2 and, as a result, low BMD (9). Among male patients who are not aromatase deficient, aside from influencing bone maturation and peak bone mass acquisition, aromatase activity may also influence body composition, even at an early age (27,28). In a study among young males aged 6-19 years old, Vandewalle et al (27,28) reported that circulating E 2 was positively associated with skeletal maturation and areal and volumetric BMD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This explains why patients with aromatase deficiency resulting from inactivating mutation of the aromatase gene show undetectable levels of E 2 and, as a result, low BMD (9). Among male patients who are not aromatase deficient, aside from influencing bone maturation and peak bone mass acquisition, aromatase activity may also influence body composition, even at an early age (27,28). In a study among young males aged 6-19 years old, Vandewalle et al (27,28) reported that circulating E 2 was positively associated with skeletal maturation and areal and volumetric BMD.…”
Section: Discussionmentioning
confidence: 99%
“…Among male patients who are not aromatase deficient, aside from influencing bone maturation and peak bone mass acquisition, aromatase activity may also influence body composition, even at an early age (27,28). In a study among young males aged 6-19 years old, Vandewalle et al (27,28) reported that circulating E 2 was positively associated with skeletal maturation and areal and volumetric BMD. In addition, lean mass in these patients was also found to positively correlate with higher testosterone levels (27).…”
Section: Discussionmentioning
confidence: 99%
“…Various alterations in hormone levels have been proposed to be responsible for this phenomenon, such as androgens [5-8], oestrogens [5-7, 9], and sex hormone-binding globulin (SHBG) [7]. Furthermore, 2 recent studies indicated that increasing insulin resistance and insulin secretion are associated with BA advancement [10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…For example, some studies evaluated the difference between BA and chronological age (CA) [8, 10], whereas others assessed the ratio between these parameters [11], while an age-adjusted indicator would theoretically be superior. Furthermore, some studies included prepubertal children only [6, 10], while others also included pubertal children [5, 7]. Additionally, most studies reported on androgen and oestrogen levels as absolute levels, although these vary significantly with age and pubertal staging, making age an important potential confounder in association studies.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, in this study, baseline testosterone concentrations were greater in normal-weight than that in obese early pubertal subjects. Lower concentrations of total testosterone with normal testicular volumes and comparable LH and FSH concentrations have been described in obese boys, associated with the progression of puberty (20,21). This phenomenon has been attributed to the reduced sex hormone-binding globulin (SHBG) binding capacity, the decreased LH pulse amplitude, and the relative increase of estrogen production (21).…”
mentioning
confidence: 99%